2008
DOI: 10.1016/j.joca.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteome of bone marrow mesenchymal stem cells from osteoarthritis patients

Abstract: In this study, we have described the differential proteome of BM-MSCs from OA patients together with an increased chemotactic response of these cells in the context of OA. These results could indicate an activation of OA BM-MSCs in response to chemotactic signals sent by the altered subchondral bone in an attempt to heal damaged tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…In contrast, disrupting the 19 actin microfilament network resulted in comparable cell deformations between shVim-20 hMSCs and shLacZ-hMSCs ( Figure 3B). Normalized aspect ratios were still slightly 21 higher for shVim-hMSCs compared to shLacZ-hMSCs, but no longer significant at both Recently, studies have found vimentin IFs to be disrupted in chondrocytes and even in 16 MSCs harvested from osteoarthritic bone marrow 4,16,27 . Because mechanical loading is without allowing for extended culture time, as previously described 33 .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, disrupting the 19 actin microfilament network resulted in comparable cell deformations between shVim-20 hMSCs and shLacZ-hMSCs ( Figure 3B). Normalized aspect ratios were still slightly 21 higher for shVim-hMSCs compared to shLacZ-hMSCs, but no longer significant at both Recently, studies have found vimentin IFs to be disrupted in chondrocytes and even in 16 MSCs harvested from osteoarthritic bone marrow 4,16,27 . Because mechanical loading is without allowing for extended culture time, as previously described 33 .…”
mentioning
confidence: 92%
“…While their role in the pathogenesis of OA is still unknown, 15 vimentin IFs have recently been found to be disrupted or dispersed in osteoarthritic 16 chondrocytes 4,16 . Notably, vimentin has also been shown to be downregulated in MSCs 17 of osteoarthritic patients 27 , which raises questions about the potential efficacy of 18 autologous stem cell therapies for treatment of OA. 19 20 The role of vimentin is still being examined using a variety of techniques to decrease, 21 disrupt, or collapse vimentin IFs, but it is clear that they are involved in modulating the 22 mechanical properties of cells.…”
mentioning
confidence: 99%
“…Testing the differentiation ability of patients with osteonecrosis by our method (grinding the entire femoral head instead of taking a 5-ml BM sample from the medullar channel) would extend our knowledge concerning the alterations at the MSC level in this bone disorder, since a higher cell number of cells within the altered milieu of the femoral head would be analyzed. More recently, Rollin et al (2008) have found, in an interesting study, that MSC from osteoarthritis (again aspirating BM cells from the femoral channel) display a different proteome and an increased chemotactic response compared with those of patients with hip fracture without osteoarthritis, but unfortunately they have not compared this with MSC obtained by standard iliac crest aspiration from the same subjects. The mild differences observed in our study Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the validation of such potential biomarkers has traditionally relied on immunoassays, specific antibodies may not be available [3], and selected reaction monitoring (SRM) has recently emerged as a promising application in medical screening due to its ability for multiplexed, high-throughput analysis as well as its sensitivity and quantitation capacity [4,5]. In a previous work we have described the regulation of several proteins in bone marrow mesenchymal stem cells (BM-MSCs) from OA patients [6]. The potential application of MSCs in cell therapies aimed at rheumatic diseases has aroused great interest [7], and our results suggested the preactivation of these cells by signaling events produced by the subchondral bone.…”
mentioning
confidence: 99%
“…All samples were obtained after patients gave their informed consent, and this study was approved by the local institutional ethics committee. After culturing the cell-containing fraction of BM aspirates as previously described [6], five pellets of approximately 2 × 10 6 confluent cells at the third passage were obtained. Then the cells were lysed, protein concentration was measured as previously described [6] and the five resulting protein extracts (110 μg each) were separated by SDS-PAGE on a 12% polyacrylamide gel.…”
mentioning
confidence: 99%